2020
DOI: 10.1039/d0ra04885b
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic instability of lithiated phosphorene

Abstract: Introduction of C improves transition capacity between intercalation and conversion reactions for multilayer phosphorene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…25 Jia et al studied the structural and electronic properties of lithium intercalated phosphorene and graphene/ phosphorene/graphene (G/P/G) sandwiches by first-principles calculations and learned that the sandwiches exhibited higher transition capacities than freestanding phosphorene. 26 Su et al studied a trilayer graphene/antimonene/graphene (G/Sb/G) heterostructure as a potential anode material for NIBs based on DFT calculations, and the calculations showed that the G/Sb/G heterostructure was thermally stable at elevated temperatures up to 500 K. The G/Sb/G heterostructure could provide a strong binding capacity and a low migration barrier for sodium, ensuring a high specific capacity and good rate capability. 27 Thus inspired by graphyne and 3D porous h-BC 2 N, 28 a new porous 3D structure 3D-PGY is designed, and on this basis to propose a sandwich-type trilayer structure graphene/PGY/graphene (G/PGY/G) using the 3D-PGY as the middle layer and two layers of graphene as the outer layer.…”
Section: Introductionmentioning
confidence: 99%
“…25 Jia et al studied the structural and electronic properties of lithium intercalated phosphorene and graphene/ phosphorene/graphene (G/P/G) sandwiches by first-principles calculations and learned that the sandwiches exhibited higher transition capacities than freestanding phosphorene. 26 Su et al studied a trilayer graphene/antimonene/graphene (G/Sb/G) heterostructure as a potential anode material for NIBs based on DFT calculations, and the calculations showed that the G/Sb/G heterostructure was thermally stable at elevated temperatures up to 500 K. The G/Sb/G heterostructure could provide a strong binding capacity and a low migration barrier for sodium, ensuring a high specific capacity and good rate capability. 27 Thus inspired by graphyne and 3D porous h-BC 2 N, 28 a new porous 3D structure 3D-PGY is designed, and on this basis to propose a sandwich-type trilayer structure graphene/PGY/graphene (G/PGY/G) using the 3D-PGY as the middle layer and two layers of graphene as the outer layer.…”
Section: Introductionmentioning
confidence: 99%